Migratie, gelijkheid & racisme - Adam, Ilke; Adefioye, Tundé; D'Agostino, Serena; Schuermans, Nick; Trauner, Florian (ASP editions - Academic and Scientific Publishers, 2021)
"Migration, Equality and Racism trigger ever more salient societal debates. More than 80 VUB academics and co-authors joined forces for this book. Philosophers, lawyers, psychologists, health scientists, sociologists, geographers, criminologists, communication and political scientists ... look at migration, equality and racism from different disciplinary angles. Together they aim to contribute to an exercise of humanism as a praxis of criticism or a 'technique of trouble-making', in the words of Edward Said. Through 44 thought-provoking and informed opinion pieces, they question widespread beliefs on migration, equality and racism and propose solutions that might disturb. Let this book be a source of inspiration for those who want to spark an informed debate on the ever more salient issues of migration, equality and racism, for those who want to learn more on how and why humanism has often remained an empty box for migrants and racialized groups. Or for those who are in search of inspiration for a just future for all. Migration, Equality and Racism is the work of Vrije Universiteit Brussel (VUB) think tank POINcaré and was created under the direction of Ilke Adam, Tundé Adefioye, Serena D'Agostino, Nick Schuermans and Florian Trauner."